Which anthropometric measures best identify excess weight in older adults? - Daniela de Assumpção; Priscila Maria Stolses Bergamo Francisco; Flávia Silva Arbex Borim; Monica Sanches Yassuda; Anita Liberalesso Neri (Brazilian Society of Geriatrics and Gerontology, 2022)
OBJECTIVES: To estimate the prevalence of and factors associated with excess weight in older adults according to body mass index (BMI), waist circumference (WC) and waist-to-height ratio (WtHR), as well as to measure the differences between the prevalences estimated by WC and WtHR in relation to BMI. METHODS: This cross-sectional study was conducted in 2016 - 2017 with 549 older adults (72-102 years) from Campinas and Ermelino Matarazzo, two cities in the state of São Paulo, Brazil. Excess weight was defined according to cut-off points established for older adults. Multiple Poisson regression analysis was performed. RESULTS: The overweight/obesity prevalences were 47.36% (BMI), 61.38% (WC) and 65.57% (WtHR), being higher in women and in those with hypertension, diabetes, polypharmacy, and normal calf circumference. They were also higher in the youngest age strata (BMI and WC), in those with arthritis/rheumatism (BMI), and in those with slow gait (WtHR). The estimated overweight/obesity prevalences according to WC and WtHR were 29.00% and 38.00% higher, respectively, than BMI. In the multiple model, there was a higher prevalence of adiposity among diabetics and those with normal calf circumference. CONCLUSIONS: Measures of abdominal adiposity provided a better diagnosis of excess weight. We recommended that health professionals consider using WtHR in anthropometric assessment of older adults, especially regarding adiposity.